Exploring the implementation of IoT in higher education: a systematic review - Yzquierdo Espinoza, Juan Diego; Moreno Ramos, Joandri Airton; Ferrer Trujillo, José Nestor; Cavada Gutierrez, Hugo Junior (LACCEI, 2025)
The current study investigates the impact of the integration of the Internet of Things (IoT) on improving academic performance in higher education students during the years 2019-2023. A systematic literature review is used to address the search problem and 26 relevant studies are identified. Methods include bibliometric data collection and qualitative compilation of results. Findings show a wide variety of tools and effects derived from the implementation of IoT in educational settings, including increased interaction between students and teachers, better resource management, and an enriched educational experience. It is the results of practical implications that are discussed, such as the need for increased support for technological infrastructure and training of teaching staff. Furthermore, the contribution of the study to understanding the emerging role of technology in higher education is highlighted. In conclusion, the importance of exploiting the opportunities offered by IoT to modernize teaching and learning in the university environment is underlined, while addressing challenges such as security and technological acceptance.